Perbandingan Efektivitas Menonton Film dengan Terapi Bermain Terhadap Penurunan Kecemasan Anak Umur 6-8 Tahun Selama Perawatan Gigi - Jainar, Rahmatika; , Dwi Kurniawati, S.KG, MPH (2016)
Anxiety is a problem of person when they are visited to dental clinical. The impact of anxiety cause delay reatments can makes increasingly the severity of dental condition. The level of dental anxiety caused many factors. The solution of dental anxiety is a distraction. The aim of this study was to compare the effectiveness of watched film and played therapy for children anxiety during dental treatment. The experiment was a quasi-experiment with pretest and posttest design. The subjects were 30 children that divide into 2 groups, 15 children with active distraction (played therapy) and 15 children with passive distraction (watched film). The rate of anxiety levels used physiological parameters such as pulse rate. The patients were quantified used pulse rate. Data analysis measured by independent t-test test. The result of independent t-test showed that the mean difference pulse on watched film as big as 3,73 meanwhile on played therapy as big as 6,20 and the value p = 0,013, there were significant difference between group pulse watched film and played therapy for children aged 6-8 years during dental treatment.